(untitled) (The Insight, 2024)
Introduction: Carpal tunnel syndrome (CTS) is the most common peripheral nerve entrapment syndrome. The high prevalence of CTS and its effect on quality of life makes it worthy of evaluation to find an effective method of treatment that would be cost-effective and satisfactory. Even though the mini-incision CT release has limited visualization, its result is promising. So, this study aimed to evaluate the outcome of the vertical mini-open technique for decompressing the carpal tunnel. Methods & Materials: This was a prospective observational study conducted in the Department of Orthopaedic Surgery, National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh during the period from January 2020 to December 2021. In our study, we included 44 diagnosed cases of carpal tunnel syndrome who underwent carpal tunnel decompression using the mini-open technique. Result: The mean age was 45.6±8.5 years with a female predominance (81.8%). The mean duration of the first occurrence of symptom to surgery was 15.8±3.2 months. The mean duration of follow-up was 26.9±2.9 weeks. The mean length of scar at the last follow-up was 19.8±1.7mm. The mean preoperative resting VAS was 7.8±1.2 which significantly decreased to 2.1±1.1 (p <0.001). The mean preoperative BCTSQ symptom severity score was 38.9±2.3 which has decreased significantly to 12.1±2 (p <0.001). Conclusion: Carpal tunnel decompression using a mini-open technique gives significant symptom and functional improvement compared to preoperative status. It is a safe approach for patients with carpel tunnel syndrome.